Lipoprotein (a) and Comprehensive Lipid Tetrad Index in Young Patients of Coronary Artery Disease - Giri, S; Rajgopalan, B; Dwivedi, S; Shrivastaba, DK; Singh, S; Kaur, I (Nepalese Heart Journal, 2004)
To compare the clinico-biochemical profile of young patients (< 40 years) having coronary artery disease (CAD) with age-sex matched controls with a special reference to lipoprotein (a) [Lp(a)] and comprehensive lipid tetrad index (CLTI).